2021
DOI: 10.1371/journal.pone.0251298
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic and secondary restless legs syndrome during pregnancy in Japan: Prevalence, clinical features and delivery-related outcomes

Abstract: Objective The aim of this study was to investigate prevalence of idiopathic and secondary restless legs syndrome (RLS) according to pregnancy trimester, and its effects on delivery-related outcomes among pregnant women in Japan. Methods This was a single-center, prospective observational study. One hundred eighty-two consecutive pregnant women participated in the study from June 2014 to March 2016. Participants were interviewed and examined in the second and third trimesters of pregnancy and 1 month after de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…With regard to the relationship between RLS and period of gestation, the results were comparable to previous studies which showed an increased tendency to develop RLS in the later trimester of pregnancy than the first trimester or postpartum period. [ 23 24 ] Of the pregnant women who were surveyed, RLS symptoms were significantly more common in the third trimester (41.0%) than in the first trimester (15.7%) and postpartum period (15.1%) ( P < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the relationship between RLS and period of gestation, the results were comparable to previous studies which showed an increased tendency to develop RLS in the later trimester of pregnancy than the first trimester or postpartum period. [ 23 24 ] Of the pregnant women who were surveyed, RLS symptoms were significantly more common in the third trimester (41.0%) than in the first trimester (15.7%) and postpartum period (15.1%) ( P < 0.001).…”
Section: Discussionmentioning
confidence: 99%